PENANAMAN KECERDASAN EMOSIONAL DAN SPIRITUAL MELALUI KEGIATAN INTRA DAN EKSTRAKURIKULER PADA MI MA’ARIF SENDANG KARANGSARI PENGASIH KULON PROGO TAHUN 2021 - Jumiyati Jumiyati (PEDIR: Journal of Elementary Education, 2022)
This study aims to determine the method of cultivating emotional and spiritual intelligence in students at MI Ma'arif Sendang Karangsari Pengasih Kulon. This research uses qualitative research, in the form of case study research. The data collection method used by the researcher is the method of observation, interviews, and documentation. In testing the validity of the research data, the researcher used a data credibility test with several techniques, including persistence of observation, triangulation (technique, source, and time), peer discussion, and using reference materials. In analyzing the data, the researcher used 3 stages, namely data reduction, presenting data in descriptive narrative form, and drawing conclusions. The results showed that the implantation of the emotional and spiritual intelligence of MI Ma'arif Sendang from the various activities carried out, had a great impact on students making children have good manners and morals, so that students were able to develop their potential in emotional and spiritual intelligence to have tawadlu nature. and and believe themselves to be fair and honest, able to control themselves, able to respect each other and respect each other, students will be motivated to participate in activities in madrasah, have noble character in daily life, students will feel happy and excited to join existing programs in madrasas so that students reach their peak, namely winning / becoming champions in every competition.